Effectiveness of Positive Reinforcement Group Guidance in Reducing Academic Procrastination - Salsabila Hayatissa'idah; Abdul Aziz Rusman (MASI Mandiri Edukasi, 2025)
Academic procrastination remains a common issue among adolescents, particularly in school settings, where students often delay completing academic tasks and struggle with time management. This study aims to determine the effectiveness of group counselling using positive reinforcement strategies in reducing academic procrastination among seventh-grade students at SMP IT Ali bin Abu Thalib Tanjung Morawa. This research employed a quasi-experimental design with a pre-test–post-test control group. A purposive sampling technique was used to select 16 students, who were assigned to an experimental group (n = 8) and a control group (n = 8). The Mann–Whitney test indicated a significant difference between the experimental and control groups, with the experimental group reporting lower levels of academic procrastination (M = 4.50) than the control group (M = 12.50). Furthermore, the Wilcoxon Signed-Rank test revealed a significant reduction in academic procrastination after the intervention (p = 0.012). These findings demonstrate that group counselling with positive reinforcement effectively reduces students’ tendencies to delay academic tasks, enhances motivation, and promotes better learning habits.